2022
DOI: 10.3389/fonc.2022.921711
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Tumor Antigens and the Immune Landscapes of Bladder Cancer Patients for mRNA Vaccine Development

Abstract: BackgroundmRNA vaccines are a novel technology that provide a potential strategy for cancer treatment. However, few studies exist that are focused on the application and development of mRNA vaccines in bladder cancer (BLCA). Therefore, this study filtered candidate antigens and specific mRNA-suitable populations in BLCA via comprehensive multi-omics analysis.MethodsClinical information, follow-up information, and gene expression profiles were obtained from the TCGA and GEO databases. Somatic mutation and DNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Gui C et al established a ferroptosis-induced tumor microenvironment landscape in bladder cancer and identified six genes as potent antigens for developing an anti-BLCA mRNA vaccine (52). Wang G et al identified AP2S1, P3H4, and RAC3 as three candidate genes of tumor-specific antigens in bladder cancer using the TCGA BLCA cohort and GSE13507 datasets (53). In contrast to these studies, we integrated four cohorts into a Meta cohort at the outset, including TCGA BLCA, GSE13507, GSE32894, and E-MTAB-4321 cohorts, which enhanced the robustness of our study.…”
Section: Successful Identification Of Tumor-associated Antigens Is Th...mentioning
confidence: 89%
See 1 more Smart Citation
“…Gui C et al established a ferroptosis-induced tumor microenvironment landscape in bladder cancer and identified six genes as potent antigens for developing an anti-BLCA mRNA vaccine (52). Wang G et al identified AP2S1, P3H4, and RAC3 as three candidate genes of tumor-specific antigens in bladder cancer using the TCGA BLCA cohort and GSE13507 datasets (53). In contrast to these studies, we integrated four cohorts into a Meta cohort at the outset, including TCGA BLCA, GSE13507, GSE32894, and E-MTAB-4321 cohorts, which enhanced the robustness of our study.…”
Section: Successful Identification Of Tumor-associated Antigens Is Th...mentioning
confidence: 89%
“…Wang G et al. identified AP2S1, P3H4, and RAC3 as three candidate genes of tumor-specific antigens in bladder cancer using the TCGA BLCA cohort and GSE13507 datasets ( 53 ). In contrast to these studies, we integrated four cohorts into a Meta cohort at the outset, including TCGA BLCA, GSE13507, GSE32894, and E-MTAB-4321 cohorts, which enhanced the robustness of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis results are generally consistent with previous studies. TTN is a commonly mutated gene in cancer and has a prominent role in predicting immune checkpoints and prognosis in solid tumours 57 . TTN mutations have been shown to be an independent risk factor for thyroid cancer and to predict a poorer prognosis for patients 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer AP2S1, P3H4, and RAC3 [174] Melanoma PTPRC, SIGLEC10, CARD11, LILRB1, and ADAMDEC1 [175] Colorectal, NSCLC, and pancreatic cancers KRAS [176] Esophageal squamous cell carcinoma (ESCC) NLRC5, FCRL4, TMEM229B, and LCP2 [177] Soft tissue sarcoma HLTF, ITGA10, PLCG1, and TTC3 [178] Glioblastoma ADAMTSL4, COL6A1, CTSL, CYTH4, EGFLAM, LILRB2, MPZL2, SAA2, and LSP1 [179] Glioma NAT1, FRRS1, GTF2H2C, BRCA2, GRAP, NR5A2, ABCB4, ZNF90, ERCC6L, and ZNF813 [180] Malignant mesothelioma FAM134B, ALDH3A2, SAV1, RORC, and FN1 [181] Stomach adenocarcinoma ADAMTS18, COL10A1, PPEF1, and STRA6 [182] Mesothelioma AUNIP, FANCI, LASP1, PSMD8, and XPO5 [183] Dosing of mRNA can be achieved by titrating up or down, depending on the need, weight, and disease state of the patient. The duration of action is intrinsically limited by mRNA degradation, reducing the likelihood of irreversible side effects, and enabling the treatment of acute indications [184,185].…”
Section: Tumor Type Neoantigen Referencementioning
confidence: 99%